Preliminary age and growth of the deep-water goblin shark Mitsukurina owstoni (Jordan, 1898) - Caltabellotta, Fabio P.; Siders, Zachary A.; Cailliet, Gregor; Motta, Fabio S.; Gadig, Otto B. F. [UNESP] (Csiro Publishing, 2020)
Owing to poorly mineralising structures, ageing deep-water elasmobranchs requires unconventional techniques. The aim of the present study was to develop an ageing method for the goblin sharkMitsukurina owstoni(Jordan, 1898) using Alcian blue staining of the vertebral column. One vertebral centrum from a male individual measuring 315.2-cm total length (TL) was aged with a minimum age of 27 years. Using a Bayesian von Bertalanffy growth model informed by back-calculated length at age, a literature search of maximum male TL, the TL of the smallest free-swimming individuals and informative priors, we estimated males grow to 374 cm TL, mature at 16 years and live up to 60 years. Our results provide useful life history information, with the aim of elucidating the cryptic biology of this deep-water shark.
Keywords: Bayesian age-growth; deep-water elasmobranchs; goblin shark; Mitsukurina owstoni